2021
DOI: 10.3390/en14175225
|View full text |Cite
|
Sign up to set email alerts
|

Denitrification Process Enhancement and Diversity of the Denitrifying Community in the Full Scale Activated Sludge System after Adaptation to Fusel Oil

Abstract: Implementation of anaerobic digestion of primary sludge in modern wastewater treatment plants (WWTPs) limits the availability of organic carbon for denitrification in conventional nitrification-denitrification (N/DN) systems. In order to ensure efficient denitrification, dosage of the external carbon source is commonly undertaken. However, application of commercial products, such us ethanol or acetate, greatly increases operational costs. As such, inexpensive and efficient alternative carbon sources are strong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 50 publications
0
1
0
2
Order By: Relevance
“…The probable reason for the differences in NUR, which, in this study, were observed between the R1 and R2 reactors, was the adaptation of the activated sludge microorganisms to mechanically treated wastewater (as a carbon source). The phenomenon of biomass adaptation and its positive influence on NUR have been reported elsewhere [30].…”
Section: Reference Substratesmentioning
confidence: 82%
“…The probable reason for the differences in NUR, which, in this study, were observed between the R1 and R2 reactors, was the adaptation of the activated sludge microorganisms to mechanically treated wastewater (as a carbon source). The phenomenon of biomass adaptation and its positive influence on NUR have been reported elsewhere [30].…”
Section: Reference Substratesmentioning
confidence: 82%
“…The paper by Kowal et al [1] deals with possibility of enhancement of nitrogen removal efficiency by the addition of external organics to a biological part of a wastewater treatment system. The experiment was conducted at a full-scale wastewater treatment plant and, as a source of organics, fusel oil, a byproduct from the distillery industry, was applied.…”
Section: An Overview Of the Contributions To This Special Issuementioning
confidence: 99%
“…Esta tem sido uma das principais rotas para a produção de biolubrificantes (BOLINA; GOMES; MENDES, 2021). É composto principalmente de álcoois com dois a cinco átomos de carbono por molécula (por exemplo, etanol, álcool n-propílico, álcool isoamílico, álcool isobutílico e álcool n-butílico (SIMSEK; OZDALYAN, 2018;KOWAL et al, 2021).…”
Section: Biolubrificante De Origem Microbianaunclassified
“…O uso e descarte adequados do óleo fúsel, como resíduo químico, é de imensa importância econômica e ambiental, o que tem sido reforçado pela crescente demanda por álcool puro, provocada pela pandemia de COVID-19, que aumentou a produção de óleo fúsel (KOWAL et al, 2021). Possíveis usos para este subproduto incluem a produção de álcoois superiores purificados por destilação simples ou fracionada e síntese química ou biotecnológica de ésteres (CHU et al, 2021).…”
Section: Biolubrificante De Origem Microbianaunclassified